Peripheral stem cell mobilization strategies in patients with autologous hematopoietic cell transplantation: A single center's experience - NAMDAROÄžLU, SÄ°NEM; Yigenoglu, TugÃ§e Nur; Batgi, Hikmettullah; Uncu Ulu, Bahar; Ä°skender, Dicle; Ã‡akar, Merih; Dal, Mehmet Sinan; AltuntaÅŸ, Fevzi (POLTEKKES KEMENKES YOGYAKARTA, 2020)
This research is to investigate the parameters which may affect the mobilization of stem cells in patients receiving autologous hematopoietic peripheral blood stem cell transplantation (PBSCT). A retrospective study was carried out using the data derived from the medical files of 242 patients who received PBSCT. Descriptive, clinical, and laboratory parameters were compared between patients with successful and unsuccessful stem cell mobilization. Successful stem cell mobilization ratio was 4.463 times higher when preemptive plerixafor was administrated; 1.032 times higher when CD34+ cell count increased 1 unit at the beginning of mobilization. The white blood cell count was inversely correlated with the success of mobilization. An increase of 1 unit in WBC count was associated with a 1.027 times decrease in the success rate. The data indicated that the administration of preemptive plerixafor and CD34+ cell count at the beginning of mobilization were directly related to the success of mobilization after PBSCT. On contrary, WBC count was inversely associated with the success rate.